Reflections Of The Vietnam Strategy On Resistance To French And Us Occupation - Leo Sianipar; Susilo Adi Purwantoro; Ignatius Eko Djoko Purwanto; Sri Sundari (CV. AFDIFAL MAJU BERKAH, 2024)
The Vietnam War against France began with the French colonization of Vietnam for nearly a century. France initially controlled South Vietnam in 1858 and expanded its influence throughout the country after the Sino-French War in 1885. This colonial rule sparked resistance from Vietnamese nationalists. The movement for Vietnamese independence gained momentum after World War II when the French tried to reclaim Vietnam. This research aims to evaluate the strategies employed by Vietnam against French and US colonialism, drawing parallels with Indonesia's fight against Dutch colonialism. Historical research methods are used to collect, analyze, and interpret past data. Various aspects, including ideology, politics, economics, and culture, influenced the relationships between the involved countries during their respective colonial periods and wars. Strengthening guerrilla warfare capabilities can provide tactical advantages for Indonesia's defense, but a balanced defense doctrine that adapts to emerging threats is essential. This approach ensures the maintenance of state security and sovereignty.